Optimal nodes selection in wireless sensor and actor networks based on prioritized mutual exclusion approach - RANGA, VIRENDER; Dave, Mayank; Verma, Anil K. (Kuwait Journal of Science, 2016)
In this research paper we study the problem of mutual exclusionin the context ofwireless sensor and actor network (WSAN) and propose two novel approaches tosolve it. The major requirements for any proposed approach in such context are: (1) theproposed approach must select the minimum number of actor nodes to act on the givenevent region, (2) the overlaps between acting ranges should be minimum, (3) wastage ofresources should be less, and finally, whole event region must be covered by one or morethan one actors as per their applicability. We have proposed two algorithms, centralizedprioritized h-out-of-k mutual exclusion algorithm (CPMEA), and distributed prioritizedh-out-of-k mutual exclusion algorithm (DPMEA) in this research paper. Both proposedapproaches construct an actor cover set with similar optimality. The simulation resultsshow the performance in terms of size of actor cover set, overlapped region, nonoverlappedregion and maximum actor coverage degree. We have also compared ourobtained results with previously proposed benchmark algorithms.